2016
DOI: 10.1007/s00436-016-5162-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and molecular characterization of Glugea serranus n. sp., a microsporidian infecting the blacktail comber, Serranus atricauda (Teleostei: Serranidae), in the Madeira Archipelago (Portugal)

Abstract: A new microsporidian infecting the connective tissue of the coelomic cavity of the blacktail comber Serranus atricauda, in the Madeira Archipelago (Portugal), is described on the basis of morphological, ultrastructural, and molecular features. The microsporidian formed large whitish xenomas adhering to the peritoneal visceral organs of the host. Each xenoma consisted of a single hypertrophic cell, in the cytoplasm of which mature spores proliferated within parasitophorous vacuoles surrounded by numerous collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The mature spores showed monomorphism with isofilar polar tube coiled into 16 turns in single layer, similar to the major Glugea species such as G. hertwigi (Lovy et al., ). However, several new Glugea species revealed different characteristics in spore type, organization and number of coils compared to the common criteria (Abdel‐Baki et al., ; Azevedo, Abdel‐Baki, Rocha, Al‐Quraishy, & Casal, ; Casal, Rocha, Costa, Al‐Quraishy, & Azevedo, ), leading to the difficulty and unreliability of species identification. Phylogenetic analysis based on SSU rDNA sequence demonstrated that G. plecoglossi fell into the Glugea subclade and was most closely related to G. anomala , G. hertwigi , Glugea sp.…”
Section: The Prevalence Of the Microsporidian In Ayu From April 2014 mentioning
confidence: 99%
“…The mature spores showed monomorphism with isofilar polar tube coiled into 16 turns in single layer, similar to the major Glugea species such as G. hertwigi (Lovy et al., ). However, several new Glugea species revealed different characteristics in spore type, organization and number of coils compared to the common criteria (Abdel‐Baki et al., ; Azevedo, Abdel‐Baki, Rocha, Al‐Quraishy, & Casal, ; Casal, Rocha, Costa, Al‐Quraishy, & Azevedo, ), leading to the difficulty and unreliability of species identification. Phylogenetic analysis based on SSU rDNA sequence demonstrated that G. plecoglossi fell into the Glugea subclade and was most closely related to G. anomala , G. hertwigi , Glugea sp.…”
Section: The Prevalence Of the Microsporidian In Ayu From April 2014 mentioning
confidence: 99%